Implementasi Logika Fuzzy dalam Mengoptimalkan Persediaan Barang dengan Metode Mamdani - Azizah Azizah; Fauziah Fauziah (Universitas Indraprasta PGRI Jakarta, 2020)
The fuzzy logic is thought to be able to map an input space into an output space. To optimize the inventory in Affan stalls can use fuzzy logic with Mamdani method. The use of fuzzy logic is necessary to optimize the inventory in Affan stalls to avoid excess items. The study method uses literature study and data analysis with the accuracy of data reaches 83%. From this analysis can know and optimize the inventory of goods in Affan stalls with method Mamdani in January 2020 get the accuracy of the data 83% with the demand of 1,500 units, sold 2,100 units and supplies required IE 2,300.